THE INFLUENCE OF WORK STRESS AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS A MEDIATING VARIABLE ON SEARCH AND RESCUE OFFICE EMPLOYEES IN WEST SUMATRA - Muhammad Fadlan; Nikolas Fajar Wuryaningrat; Ami Pujiwati (Pena Cendekia Insani, 2025)
This study aims to analyze the effect of work stress and work discipline on employee performance with work motivation as a mediating variable in Search and Rescue Office employees in West Sumatra. The study used a quantitative approach with a survey method and an associative design. The research sample consisted of 127 employees selected through total sampling with a minimum work period of six months. The research instrument was a Likert scale questionnaire with 42 statements related to work stress, work discipline, work motivation, and employee performance on a 1-5 scale. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS) to test validity, reliability, and relationships between variables, as well as hypothesis testing using bootstrapping techniques. The results showed that work discipline had a significant positive effect on employee performance, while work stress did not have a direct effect on performance. However, work stress had a significant effect on work motivation, and work motivation had a significant positive effect on employee performance. In addition, work discipline was also shown to increase work motivation. These findings confirm that optimal performance is not only influenced by discipline, but also by work motivation that can transform stress into productive drive. Thus, strengthening intrinsic motivation becomes an important strategy in improving employee performance in high-workload search and rescue agencies.